Modelling and optimization of emissions in steady state urban traffic networks. Issue 5 (2022) - Aicardi, M.; Ferro, G.; Minciardi, R.; Parodi, L.; Robba, M.
Abstract: Nowadays, to manage the increasing traffic demands, it is necessary to define methods and tools to manage traffic flows, taking into account dynamic models over a network and network-wide emissions. The paper presents an optimization model to minimize emissions in urban traffic networks in steady-state conditions. First of all, the equilibrium point assessment is carried out in the presence of constant splitting rates for each node, proving the asymptotical stability of the unique equilibrium point thanks to the direct Lyapunov method. Then, an optimization problem for minimizing emissions in steady-state is formulated and discussed, including the stability conditions. The proposed approach has been tested over a 9 nodes-12 arcs test network, showing emissions reduction in contrast to a non-optimized scenario.